2020
DOI: 10.1080/15244113.2020.1752069
|View full text |Cite
|
Sign up to set email alerts
|

Development of Adolescents’ Values and Jewish Identities via Experiential Philanthropy Education

Abstract: The values that begin to solidify during adolescence can be steered by experiential education programs designed to inculcate a set of attitudes and behaviors in their participants. One such program, Jewish Youth Philanthropy, socializes adolescents into recognizing the importance of donating both to Jewish causes and within a Jewish framework. This paper examines the relationship between these programs and the development of Jewish and donor identities during adolescence. It suggests that surveyed Jewish youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Considered to be a high impact pedagogical practice, service-learning provides students with opportunities to meaningfully enact, develop, and reflect on various identities (Astin et al, 2000; Eyler & Giles, 1999). Indeed, research has long demonstrated positive outcomes associated with service-learning (e.g., Celio et al, 2011; Tomkovick et al, 2008; Yorio & Ye, 2012) and has linked participation in service-learning to the formation of a number of identities, such as self-identity (e.g., Winans-Solis, 2014), ethnic identity (e.g., Petrov, 2013), civic and political identity (e.g., Iverson & James, 2013; Mitchell, 2015), professional identity (e.g., Beck et al, 2015; Keshwani & Adams, 2017), academic identity (e.g., Dukhan et al, 2008), and religious identity (e.g., Brookner, 2020; Rehnborg et al, 2008).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Considered to be a high impact pedagogical practice, service-learning provides students with opportunities to meaningfully enact, develop, and reflect on various identities (Astin et al, 2000; Eyler & Giles, 1999). Indeed, research has long demonstrated positive outcomes associated with service-learning (e.g., Celio et al, 2011; Tomkovick et al, 2008; Yorio & Ye, 2012) and has linked participation in service-learning to the formation of a number of identities, such as self-identity (e.g., Winans-Solis, 2014), ethnic identity (e.g., Petrov, 2013), civic and political identity (e.g., Iverson & James, 2013; Mitchell, 2015), professional identity (e.g., Beck et al, 2015; Keshwani & Adams, 2017), academic identity (e.g., Dukhan et al, 2008), and religious identity (e.g., Brookner, 2020; Rehnborg et al, 2008).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%